Problematika dalam Penyelenggaraan Pendidikan Pancasila Berdasarkan Kurikulum 2013 dan Kurikulum Merdeka - Basit, Abdul; Sapriya, Sapriya; Budimansyah, Dasim; Komalasari, Kokom; Abdillah, Fauzi (Universitas Negeri Malang, 2024)
The purpose of writing this article is to analyze the problems in the development of the Pancasila education curriculum and the implementation of Pancasila education based on the 2013 Curriculum and the Independent Curriculum. This study uses a qualitative approach with a literature study method. The results of the study indicate that the development of the Pancasila education curriculum raises public suspicion of the curriculum development process because of the large budget, is carried out without considering the results of the curriculum evaluation, and does not involve experts, academics, stakeholders, and representatives from the teacher professional association. Pancasila education based on the 2013 Curriculum has not been implemented optimally due to the availability of learning resources that are still minimal, limited time allocation, and the reduction of Core Competencies to Basic Competencies that are still balanced between aspects of attitude, knowledge, and skills. The implementation of Pancasila education based on the Independent Curriculum experiences obstacles due to the absence of limitations regarding the concept of independent learning, the unpreparedness of facilities and infrastructure, and the unclear division of learning achievements in aspects of attitude, knowledge, and skills.